1973
DOI: 10.2134/agronj1973.00021962006500020043x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Boron Effects on Protein and Oil of Corn Grain

Abstract: This study was conducted to determine the effect of nitrogen and boron on protein and oil percentages and fatty acid composition of corn (Zea mays L.) grain. In one study, two rates (90 and 180 kg/ha) of nitrogen, two periods (December and preplant), with and without a nitrification inhibitor were applied to corn on a Norfolk loamy sand soil in the Coastal Plain region of Georgia. In a second study, three rates (0.28, 0.56, and 1.12 kg/ha) of boron were applied to the same soil as for study one. Check plots wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
1
3

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
4
12
1
3
Order By: Relevance
“…This agrees with the results from Genter et al (1956), Welch (1969), Jellum et al (1973), and Jellum and Morion (1966). Based on the oil content increase in the population per se, Saratlic (1994) indicated that additive gene effects were the most important types of gene action governing this trait.…”
Section: Effect Of Selection On Genetic Parameterssupporting
confidence: 92%
“…This agrees with the results from Genter et al (1956), Welch (1969), Jellum et al (1973), and Jellum and Morion (1966). Based on the oil content increase in the population per se, Saratlic (1994) indicated that additive gene effects were the most important types of gene action governing this trait.…”
Section: Effect Of Selection On Genetic Parameterssupporting
confidence: 92%
“…Genetic factors had a much greater influence tllan did environmental factors (26). Jellum also determined that southern corn leaf blight (27) and nitrogen and boron in fertilizers did not influence fatty acid composition (28).…”
Section: Resultsmentioning
confidence: 99%
“…Welch (1969) reported that nitrogen, phosphorus, and potassium applications increased the oil concentration of corn grain slightly, but more important was that the increased grain yield resulted in greater oil production per unit of land area. In contrast, Jellum et al (1973) found that increasing nitrogen application rate had no influence on the oil concentration of corn grain.…”
mentioning
confidence: 83%